Penggunaan Aplikasi Canva Sebagai Media Pembelajaran Pembelajaran Biologi Terhadap Hasil Belajar Siswa Kelas X SMA Negeri 1 Siau Timur - Claudia Angel Putri Thanos; Ferny Margo Tumbel; Femmy Kawuwung (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The objective of this research is to assess the utilization of Canva application as a biology learning media at SMA Negeri 1 East Siau. 2. To assess the efficacy of utilizing the Canva application as a Biology learning medium in improving student learning outcomes at SMA Negeri 1 East Siau. This research instrument employs a combination of interviews, questionnaires, and test questions. Subsequently, the data is examined utilizing the percentage calculation. The research yielded a design for electronic-based media, which involved several stages: needs analysis, design, validation and revision, and testing and implementation. The effectiveness test results, validated by media experts, yielded a 95.38% rating in the highly feasible category. Similarly, the material experts rated it as very feasible with a score of 98%. Furthermore, 92.31% of students who participated in the trials found it to be very feasible. This is supported by the average pretest score of 59.3, which increased to 89.33 in the posttest, resulting in a gain score of 0.73. Therefore, utilizing the Canva application as a digital learning platform is highly appropriate for enhancing the academic achievements of 10th grade students at SMA Negeri 1 East Siau.